Risc5 y project oberon para raspberry pi (2017)
The degree project is based on the implementation of an emulator for the processor risc5 in a Raspberry pi model B in such a way that the emulator accesses the peripherals of keyboard, screen, mouse, sd directly through the software of the Raspberry Model B (low-level programming) using the Project Norebo RISC compiler emulator